Violence, Bullying, and Sexual Harassment in Tourism and Hospitality Industry: A Global Perspective (Global Journal of Human-Social Science, 2025)
The tourism and hospitality industry, while a cornerstone of global economic development and cultural exchange, is increasingly scrutinized for its endemic issues surrounding workplace violence, bullying, and sexual harassment. This sector, characterized by high employee turnover, precarious employment conditions, and power asymmetries between workers, guests, and management, presents fertile ground for such misconduct. Globally, frontline employees-often women, young workers, and migrants-are disproportionately affected, with incidents ranging from verbal abuse and intimidation to physical and sexual assault. Factors such as inadequate legal protections, cultural normalization of inappropriate behavior, and insufficient training or reporting mechanisms exacerbate the issue. Crosscultural differences further complicate definitions and responses to misconduct, making it difficult to establish universal standards. This abstract examines the scope and dynamics of these challenges across different regions, emphasizing the need for multinational policy interventions, industry-wide codes of conduct, and a shift toward inclusive and safe work environments. Addressing these issues is not only a moral imperative but also a business necessity, as worker well-being is intrinsically linked to service quality, employee retention, and the industry's long-term sustainability.
Keywords: violence; bullying; sexual harassment; tourism; hospitality